The relation between balanced need satisfaction and adolescents’ motivation in physical education - Mouratidis, Athanasios; Barkoukis, Vassilis; Tsorbatzoudis, Charalambos (European Physical Education ReviewEuropean Physical Education Review, 2015)
Self-determination theory posits that satisfaction of the needs for autonomy, competence and relatedness represents the basic nutriments for humans’ optimal functioning. It also postulates that with greater the degree to which these three needs are equally satisfied, the quality of motivation is further enhanced. Yet, this premise has remained relatively underexplored. In this correlational study, we surveyed Greek middle-school students (N = 435; 47.1% males; Mage = 13.95; SD = 0.85) and investigated to what extent balanced need satisfaction contributes over and above the need satisfaction in the prediction of quality of motivation in physical education contexts. Path analysis showed that need satisfaction along with balanced need satisfaction were linked with autonomous motivation but not with controlled motivation. The present findings imply that balanced satisfaction of the needs for autonomy, competence and relatedness can be an additional source of optimal motivation and functioning in physical education.